2000
DOI: 10.1038/sj.cdd.4400729
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Bcl-2 family members to interact with Apaf-1 in normal and apoptotic cells

Abstract: CED-9 blocks programmed cell death (apoptosis) in the nematode C. elegans by binding to and neutralizing CED-4, an essential activator of the aspartate-directed cysteine protease (caspase) CED-3. In mammals, the CED-9 homologs Bcl-2 and Bcl-x L also block apoptosis by interfering with the activation of CED-3-like caspases. However, it is unknown whether this occurs by binding to the CED-4 homolog Apaf-1. Whilst two groups previously detected an interaction between Bcl-x L and Apaf-1 in immunoprecipitates, 1,2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 45 publications
3
27
0
Order By: Relevance
“…Is the function of its mammalian Bcl-2-like counterparts primarily to buffer the action of BH3-only proteins, or like CED-9, do they act instead to control downstream mediators? Whereas mammalian prosurvival proteins do not appear to interact directly with the mammalian CED-4 homolog Apaf-1, 42,43 specific interactions with Bax 44 and Bak 45 are observed. In a manner akin to EGL-1, which indirectly triggers CED-4 activation by neutralizing CED-9, might mammalian BH3-only proteins also activate Bax/Bak indirectly by neutralizing the prosurvival Bcl-2 proteins, rather than directly as proposed ( Figure 1a)?…”
mentioning
confidence: 97%
“…Is the function of its mammalian Bcl-2-like counterparts primarily to buffer the action of BH3-only proteins, or like CED-9, do they act instead to control downstream mediators? Whereas mammalian prosurvival proteins do not appear to interact directly with the mammalian CED-4 homolog Apaf-1, 42,43 specific interactions with Bax 44 and Bak 45 are observed. In a manner akin to EGL-1, which indirectly triggers CED-4 activation by neutralizing CED-9, might mammalian BH3-only proteins also activate Bax/Bak indirectly by neutralizing the prosurvival Bcl-2 proteins, rather than directly as proposed ( Figure 1a)?…”
mentioning
confidence: 97%
“…Furthermore, despite early reports to the contrary 20,21 it is now accepted that mammalian Bcl-2 homologs do not functionally interact with APAF-1. [22][23][24] Given these significant differences, it is intriguing that the antiapoptotic functions of both Bcl-2 and CED-9 involve the mitochondria. Indeed, the functions of the mammalian Bcl-2 family members and those of CED-9/EGL-1 overlap in a number of interesting ways: despite sharing only around 22% homology with CED-9, expression of Bcl-2 inhibits apoptosis in C.elegans, 25 and Bcl-2 expression was found to rescue the excess of apoptosis found in CED-9 loss-of-function worms.…”
Section: Nematodes: Like Us Only Differentmentioning
confidence: 99%
“…The idea that a direct pathway also functions in mammals fell out of favor mainly because of the lack of evidence for a physical interaction between antiapoptotic Bcl-2 proteins and Apaf-1. 25 However, the recent analysis of mice expressing a mutant cytochrome c protein unable to bind to Apaf-1 (and hence, most likely unable to activate the apoptosome), suggests that one or more cytochrome c-independent, Apaf-1-dependent pathways do exist for the activation of caspases in mammals. 26 Mitochondria have long been thought to not play a role in apoptosis induction in C. elegans; however, the recent studies on mitochondrial fragmentation have revealed that they are more than just innocent bystanders.…”
Section: Why Two Pathways In C Elegans?mentioning
confidence: 99%